IMPROVEMENT OF MARKETING AND LOGISTICS MANAGEMENT PROCESSES TAKING INTO ACCOUNT CURRENT TRENDS IN MARKET DEVELOPMENT - FEDORENKO, MYKOLA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article investigates and considers options for the organization of marketing and logistics activities at the enterprise and developed a mechanism for managing marketing and logistics activities of the enterprise in order to implement them in the enterprise. With the help of theoretical analysis of marketing and logistics management processes and analysis of models, methods and mechanisms of marketing and logistics system of the enterprise considered the essence, purpose, content, objectives, basic principles and laws of reproduction of marketing and logistics activities in changing market conditions. the relationship of marketing and logistics at all levels of marketing and logistics strategy of the enterprise. Under the influence of marketing is the modification of the tasks of internal management and internal corporate planning of logistics activities of the enterprise. Reducing the costs of marketing and logistics strategy is one of the most affordable reserves to increase the competitiveness of the enterprise. The article examines a number of problems related to improving the management of marketing and logistics activities of the enterprise and developing an effective mechanism for its operation, adequate to the processes taking place in the market, taking into account strategic, tactical and technological aspects. Because, as utility analysis shows, a product or service provides satisfaction to the consumer only if it is available there and when the need arises, to achieve such satisfaction, integrated efforts are needed, both internal and external (with suppliers and end users). With this in mind, we need to work on understanding the importance of relations, intensifying communications between all participants in the marketing and logistics process and on the formation of information links.